Multilocus Sequence Typing Reveals a New Cluster of Closely Related Candida tropicalis Genotypes in Italian Patients With Neurological Disorders - Scordino, Fabio; Giuffrè, Letterio; Barberi, Giuseppina; Marino Merlo, Francesca; Orlando, Maria Grazia; Giosa, Domenico; Romeo, Orazio (Frontiers in Microbiology, 2018)
Candida tropicalis is a pathogenic yeast that has emerged as an important cause of candidemia especially in elderly patients with haematological malignancies. Infections caused by this species are mainly reported from Latin America and Asian-Pacific countries although recent epidemiological data revealed that C. tropicalis accounts for 6-16.4% of the Candida bloodstream infections (BSIs) in Italy by representing a relevant issue especially for patients receiving long-term hospital care. The aim of this study was to describe the genetic diversity of C. tropicalis isolates contaminating the hands of healthcare workers (HCWs) and hospital environments and/or associated with BSIs occurring in patients with different neurological disorders and without haematological disease. A total of 28 C. tropicalis isolates were genotyped using multilocus sequence typing (MLST) analysis of 6 housekeeping (ICL1, MDR1, SAPT2, SAPT4, XYR1 and ZWF1) genes and data revealed the presence of only 8 diploid sequence types (DSTs) of which 6 (75%) were completely new. Four eBURST clonal complexes (CC2, CC10, CC11 and CC33) contained all DSTs found in this study and the CC33 resulted in an exclusive, well-defined, clonal cluster from Italy. In conclusion, C. tropicalis could represent an important cause of BSIs in long-term hospitalized patients with no underlying haematological disease. The findings of this study also suggest a potential horizontal transmission of a specific C. tropicalis clone through hands of HCWs and expand our understanding of the molecular epidemiology of this pathogen whose population structure is still far from being fully elucidated as its complexity increases as different categories of patients and geographic areas are examined.